Multiwavelength analysis of the TeV-radio galaxy 3C 84/NGC 1275 - Linhoff, Lena Marie (Technische Universität Dortmund, 2021)
The radio galaxy 3C 84 is a well-studied source of radio emission and was detected as NGC1275 also in the MeV/TeV regime by gamma-ray detectors like MAGIC and Fermi-LAT. It is still unclear where and how the gamma-ray emission is produced. In this thesis, I will confine possible emission sites and exclude the region near the black hole as the origin of the gamma-ray production. For this aim, I investigate the optical depth of the broad-line region using data published by MAGIC and Fermi-LAT. Furthermore, a cross-correlation study is performed to find a possible correlation between the light curves of the two radio components in 3C84 detected by the VLBA and the gamma-ray light curve measured by Fermi-LAT. A significant correlation between the core component and the gamma-ray emission is found, which is in line with the results I derive from analyzing the optical depth of the broad-line region. For the first time, I perform a long-term analysis of NGC1275 for four years of MAGIC data, which reveals a short flare at the beginning of 2017 and a very low state of activity since then. To perform this long-term analysis, the software framework autoMAGIC was developed in the course of this thesis. autoMAGIC enables fully automatic and reproducible analyses of long-term data and can be used for the automatic processing of MAGIC data in the future.

Der aktive galaktische Kern 3C84, bekannt als Quelle von Radiostrahlung, wurde in den letzten Jahren auch von Gammastrahlungsdetektoren wie MAGIC und Fermi-LAT detektiert. Um die Entstehung der Gammastrahlung zu verstehen, grenze ich die Region ein, in der diese Strahlung entstehen kann, indem ich die Absorbtion der Gammastrahlung in der Broad-Line-Region berechne. Aufgrund dieser Studie kann die direkte Umgebung des schwarzen Lochs als Entstehungsregion ausgeschlossen werden. Außerdem führe ich eine Korrelationsanalyse der Lichtkurven der zwei bekannten radio-hellen Regionen mit der Lichtkurve im MeV/TeV-Bereich durch. Diese Analyse findet eine signifikante Korrelation zwischen der Kernkomponente der Quelle und der Fermi-LAT Lichtkurve. Im Rahmen dieser Arbeit wurde außerdem die erste Langzeitstudie der von MAGIC gemessenen hochenergetischen Gammastrahlung von NGC1275 durchgeführt. Die Ergebinisse dieser Analyse zeigen ein kurzes Aufleuchten der Quelle Anfang 2017 und danach lediglich einen sehr schwachen Fluss. Um diese Langzeitanalyse durchzuführen, wurde autoMAGIC entwickelt, ein Programm zur automatischen und reproduzierbaren Analyse der von MAGIC gemessenen Daten. autoMAGIC kann über diese Arbeit hinaus für alle Standardanalysen genutzt werden und wird maßgeblich dazu beitragen die Daten der MAGIC Kollaboration für die kommenden Jahrzehnte zu archivieren.
Keywords: Gamma-ray astronomy; Radio astronomy; MAGIC; Fermi-LAT; VLBA; 530; aktiver galaktischer Kern; Gammaastronomie; MAGIC-Teleskop; Radiofrequenzstrahlung